Looking for a dialogue between farmers and scientific soil knowledge: Learnings from an ethno-geomorphopedological study in a Philippine's upland village. Issue 1 (2nd January 2018) - Richelle, Lola; Visser, Marjolein; Bock, Laurent; Walpole, Peter; Mialhe, François; Colinet, Gilles; Dendoncker, Nicolas
ABSTRACT: Several ethnopedological studies highlight the plurality of soil knowledge and the complexity of soil knowledge systems. These knowledge systems are specific to social groups or communities and the dialogue between them is not easy. Local soil knowledge is often misrepresented and reduced when correspondences with soil sciences categories are established without due care. This paper results from two field studies in an upland village of Southern Philippines. The sociocultural richness and the high diversity of farming systems characterizing this local context have highlighted the importance of accounting for the diversity of soil knowledge related to local issues and sustainability. Looking for a dialogue among the plurality of perceptions, knowledge system, and typologies regarding soils implies that attention be given to knowledge construction processes. In order to facilitate an egalitarian dialogue it is also essential to explore relations between soil knowledge, farming systems, and sociocultural context. Discussion with farmers about their soils has cast doubt on the practical relevance of soil science knowledge in a context of non-industrial and non-chemical agriculture and revealed the dynamic dimension of farmers' soil knowledge construction and the practical relevance of contextualized knowledge. In this paper, we propose methodological and epistemological thoughts to help establish a common language between scientists and farmers. We also propose to use the soil groups emerging from field characterization as a practical tool to dialogue with farmers in the field, to build a common understanding of soil heterogeneity. We consider this approach as a critical step to initiate collaborative soil studies from a practical and endogenous perspective.